2015
DOI: 10.1386/jams.7.3.267_1
|View full text |Cite
|
Sign up to set email alerts
|

Expanding access and participation through a combination of community radio and mobile phones: The experience of Malawi

Abstract: Community radio is one of the resources that can give ordinary or disenfranchised people a voice. This opportunity can be increased through the combination of community radio and mobile phones. Using focus group discussions, face-to-face interviews and observations, this article examines how this combination can improve ordinary people’s participation in media production and in public life in Malawi. It also examines the extent to which marginalized people are using mobile phones to voice their concerns throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The benefit of such initiatives 'relates to proliferating information sources, and the ability of those traditionally positioned as receivers of development messages, to engage, ask questions, and create messages themselves' (Tacchi, 2012, p. 654). Likewise, Mhagama (2015) found that in rural parts of Malawi, where mobile phones are increasingly popular, talkback radio is providing a medium for marginalised citizens to have a public voice. Phone-in programmes to radio stations are empowering listeners 'to have a say, which has for a long time been denied to them ' (p. 278).…”
Section: Discussionmentioning
confidence: 99%
“…The benefit of such initiatives 'relates to proliferating information sources, and the ability of those traditionally positioned as receivers of development messages, to engage, ask questions, and create messages themselves' (Tacchi, 2012, p. 654). Likewise, Mhagama (2015) found that in rural parts of Malawi, where mobile phones are increasingly popular, talkback radio is providing a medium for marginalised citizens to have a public voice. Phone-in programmes to radio stations are empowering listeners 'to have a say, which has for a long time been denied to them ' (p. 278).…”
Section: Discussionmentioning
confidence: 99%
“…Despite challenges, though, press freedom is said to have improved in recent years and abuse against journalists has declined (BBC, 2019d). Radio remains the most popular medium (Mhagama, 2015b), and "in communities where there are community radio stations, the stations are helping create spaces for ordinary people to participate in public life by setting up radio listening clubs" (Mhagama, 2015a: 105). State run media from Malawi Broadcast Corporation also remains prevalent, though it has been criticized for serving the interests of the political elite (Manda 2011;Manyozo 2004;Meinhardt and Patel 2003;Patel 2000).…”
Section: Political and Media Landscapesmentioning
confidence: 99%